Creative Thinking in Science: Influence of Ethnicity, Gender and Grade Level in Co-educational Schools, Kenya - Richard Ongowo (Scientia Publica Media, 2025)
The purpose of the study was to investigate the influence of ethnicity, gender and grade level on creative thinking in science among co-educational secondary school students. The study employed cross-sectional design with purposive sampling through which 363 students were sampled from 2 co-educational secondary schools in Kakamega (n = 198) and Siaya (n = 165) counties of Kenya. The entire sample was made of grade 9 (n = 95), grade 10 (n = 99), grade 11 (n = 75), and grade 12 (n = 94) students. The same sample consisted of 168 males and 195 females. Students Science Creativity Questionnaire (SSCQ) was adapted from Smith (2019), piloted and used to measure creative thinking in science. The instrument measured four dimensions of divergent creative thinking as fluency, flexibility, elaboration and originality. The data were analysed using a 4 x 2 x 2 MANOVA. The findings indicated statistically significant ethnic differences between Luo students from Siaya county and Luhya students from Kakamega county with regard to fluency and flexibility in favor of Luhya students. There were no statistically significant gender differences in creative thinking in science and statistically significant grade level differences in the dimensions of fluency, elaboration and originality. The findings have implications for pedagogic practice. Science teachers could deliberately make learning environments characterised creative learning activities which require learners to to generate multiple ideas and encourage students to solve scientific problems. Such learning environments could be made to encourage gender inclusive pedagogic practices and tailor creative learning experiences to grade level of learners. The discussion, conclusions and recommendations of the study are herein explained.